“GESAGT IST GESAGT”: DIE SPRICHWÖRTER IM WERK VON MAX FRISCH - Nolte, Andreas (Proverbium - Yearbook, 2012)
Max Frisch (1911-1991) is arguably one of the greatest German speaking writers of the 20th century. Many of his novels and plays, but also his diaries and speeches, have earned him worldwide acclaim and a large number of studies exist that look at his work from seemingly all angles. However, one aspect – his usage of proverbial language – has not yet been recognized in any detail. While some of his well-known contemporaries, for example, Bertolt Brecht, Günter Grass, or Christa Wolf, have been regarded as “proverbial” to some degree based on existing studies, Frisch’s works have not been scrutinized in the same way. This is unfortunate, be-cause, upon careful reading of his collected works, a fairly large number of proverbs can be found in every phase of the 50 years of writing that are under review here (1931-1981). This paper attempts, therefore, to fill the existing gap by highlighting some of the roughly 300 proverbs (more than two thousand proverbial expressions are not considered in this study) that can be found in his oeuvre. It will become clear that Frisch used proverbs in many forms and contexts, both employing such phrases in their well-known original format and playing with the traditional wording. Frisch, who would have turned 100 this year (2011), undoubtedly deserves the scholarly attention from this particular perspective. His creative and extensive usage of proverbs makes this study necessary, and his stature as a writer makes it overdue.